The Relationship between Self-compassion and Depression Symptoms in the Elderly - Bunga Permata Wenny; Peggi Dwi Martika; Gusti Sumarsih Agoes; Okky Adelirandy; Mahathir (NERS Jurnal Keperawatan, 2025)
Depression can cause severe suffering among the elderly, with serious consequences such as suicide and even death. Depression in older people can be influenced by many factors, particularly physical health conditions and psychological challenges. Among the psychological aspects, self-compassion, which means as a kind and gentle attitude towards yourself when experiencing difficult times, can affect symptoms of depression in the elderly. This study aims to determine the relationship between self-compassion and depression in the elderly in the working area of public health centers (Puskesmas) in Padang. This study uses a non-probability sampling technique using a purposive sampling technique. The sample of this study was involved 176 elderly participants who visited the Lubuk Buaya Health Center, Padang City. Data collection adopted the Self-compassion Scale (SCS) questionnaire and depressive symptoms Center for Epidemiologic Studies Depression (CES-D). Pearson correlation analysis was conducted to determine the relationship between the two variables. The results showed that the average value on the SCS questionnaire was 78.56, Min 60 and Max 99 and the average value of depressive symptoms was 30.13 with a Min value of 20 and Max 42. The results of the statistical test showed that there was a moderate or fairly strong relationship between self-compassion and depressive symptoms in the elderly with a p-value of 0.000 (P <0.005), the Pearson correlation coefficient (r) value obtained was -0.413 with the direction of the relationship between the two variables being negative (-). These findings indicate that self-compassion can be recommended as a method that contributes to the emotional well-being and reduce depression among older adults.